Genomic Takeover by Transposable Elements in the Strawberry Poison Frog. (25th September 2018) - Rogers, Rebekah L; Zhou, Long; Chu, Chong; Márquez, Roberto; Corl, Ammon; Linderoth, Tyler; Freeborn, Layla; MacManes, Matthew D; Xiong, Zijun; Zheng, Jiao; Guo, Chunxue; Xun, Xu; et al.
Abstract: We sequenced the genome of the strawberry poison frog, Oophaga pumilio, at a depth of 127.5× using variable insert size libraries. The total genome size is estimated to be 6.76 Gb, of which 4.76 Gb are from high copy number repetitive elements with low differentiation across copies. These repeats encompass DNA transposons, RNA transposons, and LTR retrotransposons, including at least 0.4 and 1.0 Gb of Mariner/Tc1 and Gypsy elements, respectively. Expression data indicate high levels of gypsy and Mariner / Tc1 expression in ova of O. pumilio compared with Xenopus laevis . We further observe phylogenetic evidence for horizontal transfer (HT) of Mariner elements, possibly between fish and frogs. The elements affected by HT are present in high copy number and are highly expressed, suggesting ongoing proliferation after HT. Our results suggest that the large amphibian genome sizes, at least partially, can be explained by a process of repeated invasion of new transposable elements that are not yet suppressed in the germline. We also find changes in the spliceosome that we hypothesize are related to permissiveness of O. pumilio to increases in intron length due to transposon proliferation. Finally, we identify the complement of ion channels in the first genomic sequenced poison frog and discuss its relation to the evolution of autoresistance to toxins sequestered in the skin.